Accuracy and biasness of financial analysts. - Low, Jo Fan. (2008)
This paper evaluates the accuracy and biasness of analysts' forecasts of earnings of firms listed in the Singapore Stock Exchange(SGX).The analysts' forecasts are from the Institutional Brokers' Estimation System (I/B/E/S) for the period of April 1990 to March 2001.We compare them against four naive models and found that analysts' forecasts are more accurate to those of naive models and also improve over time horizons. This supports the arguments that analysts posses informational advantages. We found little difference in terms of forecast superiority between the local and foreign financial analysts, and that their forecasts are biased upwards.This supports the argument that the agency relationship between the brokerage firms and their clients has an effect on analysts making optimistic forecasts.